2020
DOI: 10.1039/d0cy01479f
|View full text |Cite
|
Sign up to set email alerts
|

Thermal defect engineering of precious group metal–organic frameworks: impact on the catalytic cyclopropanation reaction

Abstract: We report on the engineering of defects in precious group metal (PGM)-based HKUST-1 (Hong Kong University of Science and Technology) analogues (RhII,II, RuII,II, RuII,III) and the ramification on the catalytic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Recently, post-thermal defect-engineering (TED) was used to synthesize Ru/Rh-HKUST-1. 125,126 Afterward, various analytical techniques (e.g., VT-PXRD, FT-IR, Raman, HR-TEM, TGA, EA, N 2 , C 2 H 6 , and C 2 H 4 physisorption and COprobe FT-IR spectroscopy in UHV) were applied to analyze the reducing dimeric metal nodes and ligands upon post-thermal treatment. The results revealed that removing fragmentation could generate more open sites and partially reduce metal coordination.…”
Section: Perspectivementioning
confidence: 99%
“…Recently, post-thermal defect-engineering (TED) was used to synthesize Ru/Rh-HKUST-1. 125,126 Afterward, various analytical techniques (e.g., VT-PXRD, FT-IR, Raman, HR-TEM, TGA, EA, N 2 , C 2 H 6 , and C 2 H 4 physisorption and COprobe FT-IR spectroscopy in UHV) were applied to analyze the reducing dimeric metal nodes and ligands upon post-thermal treatment. The results revealed that removing fragmentation could generate more open sites and partially reduce metal coordination.…”
Section: Perspectivementioning
confidence: 99%
“…With these considerations in mind, we pursued a metal–organic framework (MOF)-based approach, seeking to lever a tunable pore structure to achieve selectivity and to combine this with open porosity (including periodic pore channels) and a high surface area to enhance activity. Specifically, we focused on a family of bimetallic two-dimensional (2D) MOFs, M′ 2 (OAc) 4 M″(CN) 4 2D MOF (denoted as H 2 :M′M″MOF), which allow the integration of multiple catalytic centers in their periodic structure through defect-engineering, including via thermal treatment . A thermally treated bimetallic 2D MOF with high surface area would offer enhanced exposure of catalytic sites to C 2 H 4 molecules at 1 atm of pressure; and periodic pore channels would further improve the diffusion of reactants and selectivity of 1-C 4 H 8 during C 2 H 4 dimerization reaction. , …”
Section: Introductionmentioning
confidence: 99%
“…18 A thermally treated bimetallic 2D MOF with high surface area would offer enhanced exposure of catalytic sites to C 2 H 4 molecules at 1 atm of pressure; and periodic pore channels would further improve the diffusion of reactants and selectivity of 1-C 4 H 8 during C 2 H 4 dimerization reaction. 24,25 We then prototype CO 2 to 1-C 4 H 8 , with a CO 2 -to-C 2 H 4 electrolyzer whose outlet cathodic gas is fed directly (with the aid of dehumidification) into the C 2 H 4 dimerizer and where we use the optimal MOF found herein: M′ = Ru and M″ = Ni in H 2 :M′M″MOF. We report a 1-C 4 H 8 production rate of 1.3 mol g cat −1 h −1 and a C 2 H 4 conversion of 97%.…”
Section: ■ Introductionmentioning
confidence: 99%